2017
DOI: 10.1016/j.jhydrol.2017.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Geology and geomorphology control suspended sediment yield and modulate increases following timber harvest in temperate headwater streams

Abstract: a b s t r a c tSuspended sediment transport is an important contributor to ecologic and geomorphic functions of streams. However, it is challenging to generalize predictions of sediment yield because it is influenced by many factors. In this study, we quantified the relevance of natural controls (e.g., geology, catchment physiography) on suspended sediment yield (SSY) in headwater streams managed for timber harvest. We collected and analyzed six years of data from 10 sites (five headwater sub-catchments and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 75 publications
4
28
0
Order By: Relevance
“…The standard deviation of slope was furthermore strongly correlated with standard deviation of TPI—a roughness metric. Bywater‐Reyes et al () found similar results in watersheds located in the Oregon Coast Range (PNW, USA) with suspended sediment yield varying as a function of variability in slope and a terrain roughness metric similar to standard deviation of TPI used here. Bywater‐Reyes et al () argued that the association between yields and landscape roughness metrics is likely a result of roughness being a proxy for sediment supply.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…The standard deviation of slope was furthermore strongly correlated with standard deviation of TPI—a roughness metric. Bywater‐Reyes et al () found similar results in watersheds located in the Oregon Coast Range (PNW, USA) with suspended sediment yield varying as a function of variability in slope and a terrain roughness metric similar to standard deviation of TPI used here. Bywater‐Reyes et al () argued that the association between yields and landscape roughness metrics is likely a result of roughness being a proxy for sediment supply.…”
Section: Discussionsupporting
confidence: 68%
“…Bywater‐Reyes et al () found similar results in watersheds located in the Oregon Coast Range (PNW, USA) with suspended sediment yield varying as a function of variability in slope and a terrain roughness metric similar to standard deviation of TPI used here. Bywater‐Reyes et al () argued that the association between yields and landscape roughness metrics is likely a result of roughness being a proxy for sediment supply. Bywater‐Reyes et al () found a peculiar association between high index of sediment connectivity and lower suspended sediment yields.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations